Strategi Kurikulum Dalam Meningkatkan Kemampuan Literasi Bahasa Indonesia di SMP Negeri 6 Palembang - intan nuraini; Dian Maulina (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
Reading literacy skills are the cornerstone of successful learning; however, student literacy levels in Indonesia remain relatively low according to PISA studies. This study aims to describe curriculum strategies for improving students’ reading literacy skills and to identify challenges and solutions at SMP Negeri 6 Palembang. The research method used was qualitative descriptive through observation, interviews, and documentation. The results of the study indicate that curriculum strategies are implemented through the teacher’s role as a facilitator by integrating literacy into every stage of learning, applying active methods (discussion, question-and-answer sessions, presentations), and a15-minute daily reading program. The main challenges identified include low student interest in reading, limited library facilities, and teaching methods that are sometimes still conventional. The solutions implemented include providing contextual reading materials, literacy-based assignments, and utilizing technology as an alternative learning resource.